The History and Philosophy of Ecological Psychology - Lobo, Lorena; Heras-Escribano, Manuel; Travieso, David (Frontiers in Psychology, 2018)
Ecological Psychology is an embodied, situated, and non-representational approach pioneered by J.J. Gibson and E.J. Gibson. This theory aims to offer a third way beyond cognitivism and behaviorism for understanding cognition. The theory started with the rejection of the premise of the poverty of the stimulus, the physicalist conception of the stimulus, and the passive character of the perceiver of mainstream theories of perception. On the contrary, the main principles of ecological psychology are the continuity of perception and action, the organism-environment system as unit of analysis, the study of affordances as the objects of perception, combined with an emphasis on perceptual learning and development. In this paper, first, we analyze the philosophical and psychological influences of ecological psychology: pragmatism, behaviorism, phenomenology, and Gestalt psychology. Second, we summarize the main concepts of the approach and their historical development following the academic biographies of the proponents. Finally, we highlight the most significant developments of this psychological tradition. We conclude that ecological psychology is one of the most innovative approaches in the psychological field, as it is reflected in its current influence in the contemporary embodied and situated cognitive sciences, where the notion of affordance and the work of E.J. Gibson and J.J. Gibson is considered as a historical antecedent.